Motivation for Instagram Use, Passive Instagram Use and Fear of Missing Out (FoMO) - Fransisca Iriani R Dewi; Meylisa Permata Sari (Jurnal Komunikasi, 2022)
The increase in the use of social media is an interesting phenomenon, especially for young adults. This phenomenon triggers various studies on the impact and motives of using social media. This research specifically aims to examine more deeply the phenomenon of Instagram use and the fear of loss (FoMO) in young adults. The study was conducted using a quantitative approach with an online survey method on 350 young adults (M = 20.51, SD = 1.96). The online survey consists of research information and consent forms to participate in the study; three research measuring tools (FoMO, Passive Instagram Use, and Instagram Motive); and participant demographic data. Information about this research is disseminated through Instagram Story uploads and by snowball. Statistical analysis was performed using JASP 0.14.1 (JASP Team, 2020) and IBM AMOS 21. The results of the analysis showed a good model fit and that motivation and passive use of Instagram were positively and significantly associated with FoMO with varying strengths. It was discovered that the motivation for using Instagram – dating, making new friends, academic, social connection, entertainment, self-expression, and information – did not play a significant role in FoMO, but the motivation for following and monitoring others and social recognition did. The sort of social media activity a person engages in is less essential than the type of content exposed on Instagram. Another research finding is that the relationship between motivation to use Instagram and FoMO is not mediated by passive use of Instagram.